Importance of bamboo for immediate earthquake recovery: A study from Nepal - Pramod Ghimire; Uchita Lamichhane (Advances in Bamboo Science, 2024)
This study was conducted in four districts of Nepal, Sindhupalchok, Gorkha, West Rukum and Jajarkot. It analyzed the importance of bamboo in immediate earthquake response and recovery. A total of 464 respondents were sampled from four districts struck by earthquakes. 83% of the households had bamboos on their own land, as well as trees such as Pinus spp., Castanopsis spp. and Schima wallichii. 85% of the households used bamboo for pillars, poles, and other supporting materials to hold and adjust roofing and wall materials during the time of the disasters. Moreover, 96% households believed that bamboos were highly useful and thus significant during the time of disasters such as earthquakes. People were aware of the importance of bamboo for coping with disasters; however, they were lacking appropriate knowledge about the socio-economic and environmental significance of bamboo species due to limited knowledge and research.